Peran Dinas Kebudayaan Dan Pariwisata Dalam Pengembangan Potensi Pariwisata Desa Pulosari Menjadi Desa Wisata Di Kecamatan Pangalengan Kabupaten Bandung - Emi Novariza; Ujud Rusdia; Resti resti (Jurnal Ilmu Sosial dan Ilmu Politik, 2026)
This study aims to analyse the role of the Bandung Regency Culture and Tourism Office in the development of Pulosari Village, Pangalengan District as a nature-based and community-based tourist village. The study uses a qualitative descriptive method with data collection techniques through observation, in-depth interviews, and documentation. Research informants include officials from the Culture and Tourism Office, village government, and tourism managers in the Pulosari Village area. The results show that the role of the Office covers three main aspects, namely as a motivator, facilitator, and dynamize. As a motivator, the Office plays a role in fostering community participation through training and human resource development. As a facilitator, the Office provides facilities, inter-agency coordination, and administrative support to facilitate tourism management. Meanwhile, as a dynamize, the Office functions to drive cross-party collaboration, encourage tourism product innovation, and strengthen cooperation networks between the government, communities, and business actors. However, the implementation of these three roles has not been evenly distributed across all tourist destinations in Pulosari Village. The Office is more active in certain areas such as Rahong, while several other destinations still rely on independent initiatives. This study concludes that strengthening the role of the Office in a comprehensive and sustainable manner is key to realizing an independent, innovative, and sustainable tourism village in Bandung Regency.